2015
DOI: 10.1021/je500993h
|View full text |Cite
|
Sign up to set email alerts
|

Hydrate Formation and Decomposition of CH4 and N2 in Ordered Mesoporous Carbon CMK-3 in the Presence of Tetrahydrofuran

Abstract: The use of hydrate formation in porous media is an effective method for gas storage and separation. The equilibrium isotherms of CH 4 and N 2 in CMK-3, a mesoporous carbon material, were measured under different tetrahydrofuran (THF) concentrations and temperatures. The higher is the temperature required, the greater is the formation pressure needed, but the presence of THF significantly reduces the hydrate formation pressure. When THF exists, both CH 4 and N 2 form structure II (sII) hydrate; however, the amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…THF can be used as the thermodynamic promoter to shift the hydrate phase-stability curve to lower pressure. , It is well known that THF can form a structure II hydrate in which THF molecules also fill the large cages while the gas molecules enter the small cages . Generally, carbon dioxide forms a structure I hydrate in pure water.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…THF can be used as the thermodynamic promoter to shift the hydrate phase-stability curve to lower pressure. , It is well known that THF can form a structure II hydrate in which THF molecules also fill the large cages while the gas molecules enter the small cages . Generally, carbon dioxide forms a structure I hydrate in pure water.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Generally, carbon dioxide forms a structure I hydrate in pure water. The addition of THF can affect the type of gas hydrate formation, resulting in a change in the hydrate formation pressure. When the concentration of THF is 5.1 (mol %), there is a significant change in the inflection pressure. The first inflection pressure of curve C = 5.1 (mol %) is about 0.70 MPa, which is remarkably lower than that for curve C = 0 (mol %) (1.75 MPa).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Another drawback of the hydrate separation is the unsatisfactory water–hydrate conversion ratio, which can be improved by increasing the gas–liquid contact area. Some researchers proposed that the gas–liquid contact area can be improved by dispersing water in porous materials and forming hydrates in them. Linga et al compared the growth kinetics of hydrates in wet silica sand and bulk water, and they found that the hydrate formation rate and conversion significantly improved in the former. It should be pointed out that, although this method was helpful in increasing the water–hydrate conversion ratio, the hydrate equilibrium pressure in porous materials would also increase compared with bulk water. For instance, Smith et al measured CH 4 hydrate equilibrium pressure in silica gels and observed that it shifted to a higher pressure region as compared to bulk hydrate.…”
Section: Introductionmentioning
confidence: 99%
“…The clathrate is formed by hydrogen bond of water molecules and stabilized with the occupation of a guest molecule in its center. Previous works usually focused on the phase equilibrium of gas hydrate in bulk solution. A few researches concerned the gas hydrates in porous media. Porous media with a hydrophobic surface and proper pore size can promote the kinetics of hydrate formation by enhancing gas–liquid intersurface by dispersing into mesopores and the positive effect of potential field in the mesopore. , The present work aims to study the equilibria of hydrates of CH 4 + CO 2 on ordered mesoporous carbon CMK-3. Among the three structures of gas hydrates, sI, sII and sH, CH 4 , CO 2 , and their mixtures form sI hydrates .…”
Section: Introductionmentioning
confidence: 99%